#### Answer

$y=-42$

#### Work Step by Step

$\frac{y}{-6}=6-(-1)\rightarrow$ simplify
$\frac{y}{-6}=7\rightarrow$ multiply both sides by -6
$\frac{y}{-6}\times-6=7\times-6\rightarrow$ simplify
$y=-42$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$y=-42$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.